An analysis of SABC coverage of political parties in the 2019 elections - Zulu, Nelly Teressa (Centre for Film and Media Studies, 2022)
This study critically analyses the coverage of the three main political parties (ANC, DA and EFF) in the 2019 elections by the South African Broadcasting Corporation (SABC). The SABC has been one of the main sources of information for millions of citizens across the country and many South Africans rely on the SABC for news concerning election proceedings. Therefore, the study aims to observe the role of the SABC in society, and politics during the 2019 elections in South Africa. The objective of this dissertation is to investigate whether the SABC‘s coverage was fair on the three main political parties or not. This research chose to use framing and social responsibility theory as guidelines to reliable and convincing information. Data for this research was obtained through secondary data from the SABC online channel; the study used election reports and its visuals such as pictures, videos for analysis. The study further used videos from the beginning of 2019 election campaigns, until the last day of elections which was scheduled on the 10th of May 2019. According to the research findings, the SABC did not represent the real image of the political parties which may be regarded as unprofessional and may taint the quality of their work. The research shows that in the media there are deep-rooted social and cultural issues that need transformation. The studies notes that media reforms can be the solution to some of the issues discussed in this dissertation. During election period the media was seen as bias, giving more coverage to the ruling party and this conduct led many to conclude that the SABC was used as a mouthpiece of certain political parties. However, the study also observed that there are traditional news factors that influenced the news selection.